REKOMENDASI PENGENDALIAN PERSEDIAAN BAHAN BAKU SYNTHETIC LEATHER MENGGUNAKAN METODE EOQ DI PT. SINJARAGA SANTIKA SPORT - Jalil Anwar, Hoerul; Susandi, Dony (Universitas Majalengka, 2019)
Optimal raw material inventory is an important factor in the process of smooth production of a company. This raw material can be controlled by certain method, one of mhich is the EOQ method which has a higher accuracy rate than conventional methods. PT. Sinjaraga Santika Sport is a company engaged in the ball manufacturing industry, with its main orientation is making soccer balls. Where the main raw materials are fabrics, threads, inner tubes, glue, and several other additional raw materials such as nipples, nets and ink. This study aims to analyze the frequency of purchases and the purchase amount of synthetic leather optimal raw materials, time for ordering raw material (reorder point), safet reserve raw material (safet stock), maximum inventory and the comparison between total inventory costs company policies using the EOQ method in the company.The result of this study were obtained from the optimal purchase of synthetic leather raw materials according to the calculatuin of the EOQ method is 8557,9 meters with the number of purchases as much as 3 times in total and the total cost of supply is Rp 5.987.400, while the number of companies 12 times in the amount according to the number of purchases as expected 2313,3 meters and the total cost of supplies is Rp 11.908.267, then it can be concluded thet using the EOQ method produces more efficiency because there are cost saving of Rp 5.920.867.To anticipate underirable matters related to syntehtic leather raw materials supplies, the EOQ method provides advice to provide the safety stock of 118,7 meters, while for the maximum point the supply may not exceed 8698,6 meters. And reorder when raw material supllies are at the level of 919 meters.